Mildew-proof flame-retardant environment-friendly bio-based adhesive as well as preparation method and application thereof

By forming a multiple crosslinking system with lignin furfural resin with hyperbranched polymer crosslinking agent HBPB and trivalent metal salt, the problem of inadequate environmental protection and mildew-proof flame retardant performance of phenolic resin adhesive is solved, and the preparation of high-performance environmentally friendly bio-based adhesive is realized.

CN120248798APending Publication Date: 2025-07-04NANJING TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510555205.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-29
Publication Date
2025-07-04

AI Technical Summary

Technical Problem

The existing phenolic resin adhesives have high formaldehyde emission, are not environmentally friendly, and lack anti-mold and flame retardant properties, which limits their application. There are bottlenecks in performance improvement of biomass-based adhesives.

Method used

The lignfurfural resin is used to combine with the hyperbranched polymer crosslinking agent HBPB and trivalent metal salts (such as ferric chloride), and a multiple crosslinking enhancement system is formed through hydrogen bonds, covalent bonds and metal ion coordination bonds to enhance the anti-mold and flame retardant properties of the adhesive.

Benefits of technology

It significantly improves the adhesive strength, mildew resistance and flame retardancy, realizes the green production of environmentally friendly bio-based adhesives, and broadens its application areas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120248798A_ABST
    Figure CN120248798A_ABST
Patent Text Reader

Abstract

The invention discloses a mildew-proof flame-retardant environment-friendly bio-based adhesive as well as a preparation method and application thereof, a bio-based phenolic resin adhesive is synthesized from sodium lignin sulfonate and furfural, a green production way is provided for phenolic resin production, and a technically perfect, economically feasible implementation scheme is provided for biomass resource comprehensive utilization. The hyperbranched polymer cross-linking agent and the trivalent metal ions are added, and multiple cross-linking enhancing systems such as hydrogen bonds, covalent bonds and metal ion coordination bonds are adopted for modification, so that the mechanical property of the resin is greatly improved; meanwhile, phenylboronic acid and trivalent metal ions are introduced into the hyperbranched polymer, so that the mildew resistance and flame retardance of a bio-based adhesive system are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of green adhesive materials, and particularly relates to a mildew-proof, flame-retardant and environment-friendly bio-based adhesive and its preparation method and application. Background Art

[0002] At present, the resins used in the wood-based panel and furniture industries mainly include "three aldehyde" resins, namely phenolic resin (PF), urea-formaldehyde resin (UF) and melamine-formaldehyde resin (MF). Phenolic resin is a synthetic resin that was industrially produced in 1909. It is formed by the condensation reaction of phenolic compounds and aldehyde compounds under acidic or alkaline catalysts. Phenolic resin adhesives have the advantages of low formaldehyde release, excellent water resistance and good weather resistance, and are the main adhesives used for outdoor-grade plywood and container floors. With the improvement of people's living standards, the use of "three aldehyde resins" is restricted. On the one hand, the consumption of petroleum has been increasing year by year, resulting in a shortage of petroleum resources; on the other hand, since the raw materials for preparing "three aldehyde resins" contain harmful formaldehyde, the large-scale production of phenolic resin poses a great threat to the environment.

[0003] Bio-based adhesives have become one of the focuses of research by scientific researchers due to their environmental protection, renewable nature and low price. Such adhesives can prevent formaldehyde release at the source and reduce the harm to the environment and human body. Adhesives made from natural organisms as raw materials have the advantages of wide sources, degradability and non-toxicity.

[0004] Lignin is an important component of plants, accounting for about 30% of the organic carbon content in nature. It is an important natural renewable biomass macromolecule. Due to its large output and recyclability, lignin has broad application prospects in the fields of wood processing, chemical engineering, energy, etc. In previous research applications, lignin has a relatively complex chemical structure and low reactivity due to its source and production process. For a long time, it has only appeared in low-end products such as fuels, additives and dispersants as waste, and has not been well developed and utilized. Among the many research directions of lignin, since lignin plays a role in bonding cellulose and hemicellulose in plants, it can be regarded as a natural adhesive in plants. From a chemical structure perspective, the phenolic hydroxyl groups, carboxyl groups and unreacted active sites in its benzene ring structure all provide the possibility of reaction as an adhesive, and there is a theoretical basis for preparing wood adhesives.

[0005] During the preparation and use of natural biomass resin adhesives, zero emissions of harmful substances can be achieved, which is beneficial to human health and reduces environmental pollution at the same time. Furfural comes from the processing residues of agricultural and forestry crops such as corn, wheat, and sugarcane. It has a stable furan ring and hydroxymethyl group, and has good heat and water resistance. As an aldehyde of biomass, it not only has an environmentally friendly source and little harm to the environment, but also can relieve the tension of global oil resources. However, the existing phenolic resin adhesives have problems of high phenol and formaldehyde content and lack of environmental protection. At the same time, they do not have the properties of mildew prevention and flame retardancy, which limits their development. Summary of the Invention

[0006] Object of the Invention: The technical problem to be solved by the present invention is to provide an environmentally friendly bio-based adhesive with mildew prevention and flame retardancy properties in view of the deficiencies of the prior art, to provide a green production route for phenolic resin production, and to provide a technically perfect and economically feasible implementation plan for the comprehensive utilization of biomass resources.

[0007] In order to achieve the above object of the invention, the technical solutions adopted by the present invention are as follows: An environmentally friendly bio-based adhesive with mildew prevention and flame retardancy, comprising the following components by mass fraction: 100 parts by weight of lignin furfural resin; Hyperbranched polymer crosslinking agent HBPB: 1-2 parts by weight; Trivalent metal salt: 2-6 parts by weight.

[0008] Specifically, the lignin furfural resin is prepared by the following steps: S1-1: Dissolve lignin in an alkali solution and stir at high speed to obtain a lignin solution; S1-2: Add furfural to the lignin solution obtained in step S1-1 and react by heating in stages; S1-3: After the reaction is completed, cool to room temperature to obtain lignin furfural resin.

[0009] Further, in step S1-1, the lignin is sodium lignosulfonate, and the alkali solution is a 0.5-1 mol / L NaOH aqueous solution; the stirring rate at high speed is 100-150 r / min, and the stirring time is 5-10 min; the solid-liquid ratio of lignin to alkali solution is 1:2-5, in g / mL.

[0010] Further, in step S1-2, the mass ratio of lignin to furfural is 0.6-0.8:1, the temperature is raised to 60-65 °C in the first stage and reacted for 40-50 min, the temperature is raised to 90-120 °C in the second stage and reacted for 2-6 h, and the stirring rate is 250-300 r / min.

[0011] Specifically, the hyperbranched polymer crosslinking agent HBPB is prepared through the following steps: S2-1: Add succinic anhydride and diethylenetriamine into a reactor at a molar ratio of 0.8 - 1.2:1, heat and stir evenly; S2-2: Continuously raise the temperature and stir the mixture obtained in step 2-1. After reacting for a period of time, cool it to room temperature to obtain a yellow solid HBPA; S2-3: Disperse HBPA in deionized water to obtain an HBPA solution, then add an acidic solution and adjust the pH to neutral; S2-4: Continuously add 3-formylphenylboronic acid, raise the temperature and stir until the reaction is complete, then it is obtained.

[0012] Furthermore, in step 2-1, the reaction temperature is 55 - 60 °C, the reaction time is 1.5 - 2 h, and the stirring rate is 150 - 200 r / min; in step 2-2, the reaction temperature is 140 - 155 °C, the reaction time is 3 - 4 h, and the stirring rate is 250 - 300 r / min.

[0013] Furthermore, in step 2-3, the concentration of the HBPA solution is 8 - 10 wt%, and the acidic solution is a 20 - 30 wt% HCl solution; in step 2-4, the molar ratio of 3-formylphenylboronic acid to HBPA is 0.6 - 0.8:1; the temperature is 120 - 140 °C, the reaction time is 6 - 12 h, and the stirring rate is 250 - 300 r / min.

[0014] Specifically, the trivalent metal salt is ferric chloride, aluminum chloride or chromium chloride, preferably ferric chloride. Through research, it is found in the present invention that when the above-mentioned FeCl3 is used, the comprehensive performance of the adhesive, especially the bonding strength, mildew resistance and flame retardancy, is better.

[0015] In the present invention, by adding a hyperbranched polymer crosslinking agent and a trivalent metal salt, the mechanical properties of the resin are greatly improved through a multiple crosslinking enhancement system such as hydrogen bonds, covalent bonds and metal ion coordination bonds. At the same time, the boronic acid and trivalent metal ions introduced into the hyperbranched polymer improve the mildew resistance and flame retardancy of the bio-based adhesive system.

[0016] As a major component of plants, lignin is also a sustainable raw material. However, due to its structure, it is difficult to be synthesized into plastics alone. The large number of phenolic hydroxyl groups in lignin make it possible to replace phenol when synthesizing lignin-based adhesives. By using all-biomass lignin and furfural to replace phenol and formaldehyde, a lignin-furfural resin adhesive with mildew-proof and flame-retardant effects was prepared. The hyperbranched polymer crosslinker forms borate ester bonds with catechol groups in lignin to produce covalent crosslinking and construct a covalent crosslinking network. At the same time, the amino groups in the hyperbranched polymer crosslinker form hydrogen bonds with phenolic hydroxyl groups in lignin, increasing the cohesion of the adhesive and thus improving the bonding strength and water resistance; metal ions form bonds with phenolic hydroxyl groups. During the stretching process, the coordination bonds can act as sacrificial bonds to dissipate energy, improving the toughness of the glue layer; the formed hydrogen bonds and coordination bonds improve the anti-shear ability of the adhesive, thereby increasing the viscosity and improving the initial tack of the adhesive; the phenylboronic acid group in HBPB can inhibit the synthesis of cell walls and increase the mildew resistance of the adhesive. At the same time, phenylboronic acid has lower toxicity and is more easily degradable compared to traditional mildew-proof agents (such as organic mercury and phenols); inorganic metal ions promote the dehydration and carbonization of phenolic resin during combustion to form a char layer. The char layer acts as a physical fire barrier, hindering the penetration of external oxygen and delaying the decomposition of internal combustible substrates. At the same time, phenylboronic acid will form a unique "boron oxygen six-membered ring" structure at high temperatures. The two work together to enhance the flame retardancy of the adhesive.

[0017] Furthermore, the preparation method of the above-mentioned mildew-proof, flame-retardant and environmentally friendly bio-based adhesive is also within the protection scope of the present invention. Mix the lignin-furfural resin, hyperbranched polymer crosslinker and trivalent metal salt at room temperature and stir until a uniform gel state is presented to obtain the product.

[0018] Furthermore, the present invention also claims the application of the above-mentioned mildew-proof, flame-retardant and environmentally friendly bio-based adhesive in the processing of wood-based panels.

[0019] Specifically, apply the adhesive to the wood veneer, and then perform blank assembly and hot pressing.

[0020] Preferably, the preparation process of the plywood includes: according to the coating amount of 180 g / m 2 roll coat the environmentally friendly adhesive on one side of a 400 mm×400 mm×1.6 mm wood veneer using a coating roller. Assemble and blank the veneer of the core layer with the adjacent upper and lower veneers in a vertical direction. Then, place the assembled veneer on a metal backing plate, fix the blanked veneer with the metal backing plate, and then place it on a CGYJ-100 hot press. Adjust the press parameters to a pressure of 2.5 MPa, a temperature of 180 °C and a time of 480 s for hot pressing.

[0021] Preferably, the wood veneer used can be one or more of poplar veneer, eucalyptus veneer, pine veneer and Chinese fir; preferably, the water content of the wood veneer is controlled at 8-12%.

[0022] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention prepares an environmentally friendly adhesive based on lignin furfural resin modified by metal ions and hyperbranched crosslinking agent HBPB, which is beneficial to improving the strength and toughness of the protein adhesive, and at the same time improves the mildew resistance and flame retardancy of the adhesive, and helps to broaden the application fields of lignin composites.

[0023] (2) The preparation raw materials of the present invention, including lignin and furfural, are renewable resources, which have the characteristics of wide raw material sources, strong renewable ability, green environmental protection, low price, etc., and reduce the overuse of non-renewable resources.

[0024] (3) The adhesive prepared by the present invention is green and pollution-free, does not produce harmful components such as formaldehyde, and will not cause harm to the environment and human health.

[0025] (4) The process in the present invention is easy to operate, does not require complex machinery and equipment, and is conducive to actual industrial promotion. Description of the Drawings

[0026] The following further specific description of the present invention is made in conjunction with the drawings and specific embodiments, and the above and / or other advantages of the present invention will become clearer.

[0027] Figure 1 shows the growth of mold on the samples measured in each example and comparative example.

[0028] Figure 2 shows the test results of the flame retardant performance of the adhesives of the samples measured in each example and comparative example. Specific Embodiments

[0029] According to the following examples, the present invention can be better understood.

[0030] For those not specifying specific techniques or conditions in the examples, they shall be in accordance with the techniques or conditions described in the literature in this field or in accordance with the product specifications. All reagents or instruments not indicating the manufacturer can be obtained as conventional products through regular channels.

[0031] The lignin involved in the examples is sodium lignosulfonate, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0032] The furfural and diethylenetriamine involved are purchased from Shanghai Macklin Biochemical Co., Ltd.

[0033] The succinic anhydride and anhydrous ferric chloride involved were purchased from Nanjing Wanqing Chemical Glass Instrument Co., Ltd.

[0034] The preparation method of the lignin furfural resin in the examples is as follows: Dissolve 25 g of sodium lignosulfonate in 55 ml of sodium hydroxide solution with a concentration of 0.5 mol / L, then add 31.33 g of furfural, raise the temperature to 65 °C and react for 40 minutes, then raise the temperature to 120 °C and continue to react for 2 hours, and cool to room temperature to obtain a black liquid, which is the lignin furfural resin.

[0035] The preparation method of the hyperbranched polymer crosslinker HBPB in the examples is as follows: React succinic anhydride and divinyltriamine (0.8 mol∶1 / mol) at 50 °C for 2 hours. Subsequently, raise the temperature to 140 °C and continue heating for 3 hours. Finally, cool the reaction mixture to room temperature to obtain a yellow solid HBPA. Disperse the synthesized HBPA in deionized water to a content of 8 wt%, obtain a light yellow solution, and adjust the pH of the solution to 9 using 20 wt% HCl. Add 3-formylphenylboronic acid (PDBA) according to the ratio of HBPA and 3-formylphenylboronic acid (0.8 mol∶1 / mol), raise the temperature to 80 °C and react for 20 hours, and the resulting solution is the hyperbranched polymer HBPB. Example 1

[0036] Weigh each component according to the weight ratio, mix 25 g of lignin furfural resin, 0.5 g of hyperbranched polymer HBPB, and 0.5 g of anhydrous ferric chloride at room temperature, and stir until a uniform gel-like state is presented, then it is obtained. Example 2

[0037] Weigh each component according to the weight ratio, mix 25 g of lignin furfural resin, 0.5 g of hyperbranched polymer HBPB, and 1 g of anhydrous ferric chloride at room temperature, and stir until a uniform gel-like state is presented, then it is obtained. Example 3

[0038] Weigh each component according to the weight ratio, mix 25 g of lignin furfural resin, 0.5 g of hyperbranched polymer HBPB, and 1.5 g of anhydrous ferric chloride at room temperature, and stir until a uniform gel-like state is presented, then it is obtained.

[0039] Control Example 1 Compared with Example 1, hyperbranched polymer HBPB and trivalent metal ions were not added in Control Group 1.

[0040] Control Example 2 Compared with Example 1, trivalent metal ions were not added in Control Group 2.

[0041] Control Example 3 Compared with Example 1, hyperbranched polymer HBPB was not added to Control Group 1.

[0042] Test Example Use the bio-based adhesives obtained from the above Examples 1-3 and Comparative Examples 1-3 to prepare three-layer plywood. The specific preparation process is as follows: Use poplar veneer with a size of 400mm×400mm×1.6mm as the plywood substrate, and control the moisture content of the poplar veneer at 8%-12%. When preparing, apply the bio-based adhesive on one side of the veneer substrate by roller coating at a coating amount of 180g / m 2 . When assembling the three-layer plywood, the veneer in the core layer is vertically arranged and assembled with the adjacent upper and lower veneers. The hot pressing parameters are set as a pressure of 2.5MPa, a temperature of 180°C, and a time of 480s. After continuous hot pressing, take out the prepared three-layer plywood from the press.

[0043] Testing of adhesive bonding performance, toughness and water resistance: According to the test methods for physical and chemical properties of wood-based panels and veneered wood-based panels in GB / T 17657-2013, test the dry bonding strength, fracture toughness and wet bonding strength of the plywood prepared with the adhesive. Among them, the fracture toughness reflects the toughness of the adhesive, and the wet bonding strength reflects the water resistance of the adhesive. The test results are shown in Table 1.

[0044] Testing of adhesive mildew resistance: Evenly apply 0.5g of uncured adhesive on poplar splints (25x80x3mm), place the splints in a drying dish that has been disinfected with disinfectant and high temperature (120°C), maintain a relative humidity of 99%, and place them in an oven at a constant temperature of 35°C. Monitor the growth of mold on the samples through a camera, and the results are shown in Figure 1 .

[0045] It can be seen that: the hyperbranched polymer HBPB and the lignin furfural resin adhesive enhanced by trivalent metal ions of the present invention have a significant mildew-proof effect. The reason for such a good mildew-proof effect may be that lignin furfural resin, HBPB and trivalent metal ions form a denser cross-linked structure on the wood surface, reducing cracks and pores, thereby restricting the conditions for mold growth and inhibiting the growth and reproduction of mold. On the other hand, because boron, as a commonly used preservative for environmentally friendly wood, can achieve the effect of mildew prevention and corrosion prevention by inhibiting the growth of microorganisms. At the same time, due to the strong oxidizing and corrosive properties of ferric chloride, it can undergo an oxidation reaction with the organic substances produced by mold, thereby destroying the cell membrane structure of mold and killing mold, and the antibacterial activity inherent in the Schiff base structure in HBPB improves the mildew resistance.

[0046] Table 1 Bonding strength of plywood

[0047] Flame retardancy test of the adhesive: According to ISO 5660-1, the maximum heat release rate of the adhesive sample was tested on an FTT cone calorimeter with a heat flux of 50 kW / m 2 , and the test results are shown in Figure 2 .

[0048] It can be seen that: the hyperbranched polymer HBPB and the trivalent metal ion-enhanced lignin furfural resin of the present invention have excellent flame retardancy, mainly because the grafted phenylboronic acid is contained in HBPB. When the organic boride undergoes pyrolysis, a glassy molten covering will be formed, covering the surface of the polymer to isolate heat and air. The organic boron compound can promote the carbonization of the material and generate a carbon layer with good thermal stability. Metal elements such as trivalent iron ions can catalyze the dehydration and chain scission of the polymer matrix and form a stable carbon layer, thereby effectively inhibiting the heat / smoke release during the combustion process. The excellent flame retardancy of the adhesive of the present invention is the result of the synergistic effect of each component.

[0049] The present invention provides an idea and method for a mildew-proof, flame-retardant and environmentally friendly bio-based adhesive, its preparation method and application. There are many methods and ways to specifically implement this technical solution. The above description is only the preferred embodiment of the present invention. It should be noted that for those of ordinary skill in the art, without departing from the principle of the present invention, several improvements and modifications can be made, and these improvements and modifications should also be regarded as the protection scope of the present invention. Each component not clearly defined in this embodiment can be realized by the prior art.

Claims

1. A mildew-proof, flame-retardant and environmentally friendly bio-based adhesive, characterized in that, It comprises the following components by mass parts: 100 parts by weight of lignin furfural resin; Hyperbranched polymer crosslinking agent: 1 - 2 parts by weight; Trivalent metal salt: 2 - 6 parts by weight.

2. The anti-mildew, flame-retardant and environmentally friendly bio-based adhesive according to claim 1, characterized in that, The lignin furfural resin is prepared through the following steps: S1-1: Dissolve lignin in an alkali solution and stir at high speed to obtain a lignin solution; S1-2: Add furfural to the lignin solution obtained in step S1-1 and raise the temperature in stages for reaction; S1-3: After the reaction is completed, cool to room temperature to obtain lignin furfural resin.

3. The anti-mildew, flame-retardant and environment-friendly bio-based adhesive according to claim 2, wherein In step S1-1, the lignin is sodium lignosulfonate, and the alkali solution is a 0.5 - 1 mol / L NaOH aqueous solution; the stirring rate of the high-speed stirring is 100 - 150 r / min, and the stirring time is 5 - 10 min; the solid-liquid ratio of the lignin to the alkali solution is 1:2 - 5, in g / mL.

4. The anti-mildew, flame-retardant and environment-friendly bio-based adhesive according to claim 2, wherein In step S1-2, the mass ratio of lignin to furfural is 0.6 - 0.8:

1. Heat to 60 - 65 °C in the first stage and react for 40 - 50 min, then heat to 90 - 120 °C in the second stage and react for 2 - 6 h, and the stirring rate is 250 - 300 r / min.

5. The anti-mildew, flame-retardant and environment-friendly bio-based adhesive according to claim 1, wherein The hyperbranched polymer crosslinking agent is prepared through the following steps: S2-1: Add succinic anhydride and diethylenetriamine to the reactor in a molar ratio of 0.8 - 1.2:1, heat and stir evenly; S2-2: Continue to raise the temperature and stir the mixture obtained in step 2-1, continue to react for a period of time, and then cool to room temperature to obtain a yellow solid HBPA; S2-3: Disperse HBPA in deionized water to obtain an HBPA solution, and then add an acidic solution and adjust the pH to neutral; S2-4: Continue to add 3-formylphenylboronic acid, raise the temperature and stir to react fully, and then obtain it.

6. The anti-mildew, flame-retardant and environmentally friendly bio-based adhesive according to claim 5, characterized in that, In step 2-1, the reaction temperature is 55 - 60 °C, the reaction time is 1.5 - 2 h, and the stirring rate is 150 - 200 r / min; in step 2-2, the reaction temperature is 140 - 155 °C, the reaction time is 3 - 4 h, and the stirring rate is 250 - 300 r / min.

7. The anti-mildew, flame-retardant and environmentally friendly bio-based adhesive according to claim 5, wherein In step 2-3, the concentration of the HBPA solution is 8 - 10 wt%, and the acidic solution is a 20 - 30 wt% HCl solution; in step 2-4, the molar ratio of 3-formylphenylboronic acid to HBPA is 0.6 - 0.8:1; the temperature is 120 - 140 °C, the reaction time is 6 - 12 h, and the stirring rate is 250 - 300 r / min.

8. The anti-mildew, flame-retardant and environment-friendly bio-based adhesive according to claim 1, characterized in that, The trivalent metal salt is ferric chloride, aluminum chloride or chromium chloride, preferably ferric chloride.

9. The preparation method of the mildew-proof, flame-retardant and environment-friendly bio-based adhesive according to any one of claims 1 to 8, characterized in that, Mix the lignin furfural resin, hyperbranched polymer crosslinking agent and trivalent metal salt at room temperature, and stir until a uniform gel state is presented to obtain it.

10. Application of the mildew-proof, flame-retardant and environmentally friendly bio-based adhesive according to any one of claims 1 to 8 in the processing of wood-based panels.